2021
DOI: 10.18632/aging.203154
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis reveals an immunological role and prognostic potential of PXN in human cancer

Abstract: Paxillin (PXN) is a protein involved in numerous physiological processes, and its presence is closely related to the occurrence and development of many types of tumors. However, no studies have analyzed PXN from a pancancer perspective. We analyzed PXN expression, immune cell infiltration, prognosis, and biological function across different types of tumors included in The Cancer Genome Atlas and Gene Expression Omnibus datasets. The results showed that expression of PXN varies in different tumors. Expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Pan-cancer analysis focuses on studying alterations in DNA, RNA and protein levels in different human tumor types to reveal genes associated with tumor development, which is important for cancer prevention and improving patient survival ( Chen et al, 2021 ; Lu et al, 2021 ). As an epigenetic regulatory molecular, RNA N6-methyladenosine plays a crucial role in the development and progression of cancer ( Wang et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%
“…Pan-cancer analysis focuses on studying alterations in DNA, RNA and protein levels in different human tumor types to reveal genes associated with tumor development, which is important for cancer prevention and improving patient survival ( Chen et al, 2021 ; Lu et al, 2021 ). As an epigenetic regulatory molecular, RNA N6-methyladenosine plays a crucial role in the development and progression of cancer ( Wang et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%
“…The network markers indicated that endothelium, oxidative stress, and inflammation have important roles in atherosclerosis; the top-ranked genes (by degree) and their corresponding functions are shown in Table 4 ( Yang et al, 2000 ; Zhang, 2013 ; Schisler et al, 2015 ; Mezzadra et al, 2017 ; Zheng et al, 2017 ; Guan et al, 2018 ; Lan et al, 2020 ; Nie et al, 2020 ; Zheng et al, 2020 ; Chen et al, 2021a ; Cao et al, 2021 ; Covarrubias et al, 2021 ; Liu et al, 2021 ; Wang et al, 2021 ; Zheng et al, 2021 ). For example, the gene with the largest degree was PXN, which encodes a cytoskeleton protein.…”
Section: Resultsmentioning
confidence: 99%
“…PXN, as an important part of the focal adhesion complex, was correlated with poor clinical outcomes in patients with tumors [ 27 ]. Chen et al [ 28 ] reported that abnormal PXN expression was related to poor prognosis, immune infiltration, and protein phosphorylation in different tumor types. Upregulated PXN expression was linked to shorter OS in OV from public data platform.…”
Section: Discussionmentioning
confidence: 99%